Analysis of the Solution Behavior of the Bernoulli Dynamic Equations on Time Scales - Ahrendt, Chris R.; Nunn, Caleb; Lehnen, Matthew; De Valk, Claudia (My University, 2018)
We analyze the behavior of solutions of the dynamic form of the Bernoulli equation after deriving it using the time scale calculus. To do this, we transform the first-order linear equation into a logistic form of the equation and then make an appropriate substitution
Color poster with text and images.
Keywords: Posters; Time scales; Bernoulli equation; Mathematics